(untitled) - Kado, Clarence I (St. Paul, 2010)
Plant Bacteriology is a scholarly, scientific compendium of the latest known information about bacterial diseases affecting modern plants, from agricultural crops to wild growth. Written for intermediate to advanced students and experts in the field, Plant Bacteriology's chapters cover "Evolution of Bacterial Pathogens", "Rapid Necrotizing Diseases", "Asymptomatic and Latent Infections", "Epidemiology and Control of Bacterial Plant Diseases", and much more. Full-color photographs illustrate this studious, meticulously researched and detailed text, ideal for specialist and college library collections
Keywords: Bacterial diseases of plants,Phytopathogenic bacteria,Bệnh do vi khuẩn ở thực vật,Bệnh học vi khuẩn thực vật